Corporate governance-based strategic approach to sustainability in energy industry of emerging economies with a novel interval-valued intuitionistic fuzzy hybrid decision making model - Qi, Wenhao; Huang, Zhixiong; Dinçer, Hasan; Korsakiene, Renata; Yüksel, Serhat (MDPI, 2020)
The sustainability in energy industry is one of the most prominent issues in emerging economies because of needs for the long-term growth of production and managerial capacity. Accordingly, corporate governance could lead to develop the sustainable production of energy industry. The purpose of this study is to define a set of criteria and dimensions for analyzing the corporate governance-based strategic approach to sustainability in the energy industry of emerging economies. For this purpose, this study provides several novelties by extending a hybrid decision making model with interval-valued intuitionistic fuzzy sets (IVIF) and defining the related criteria and dimensions of corporate governance-based strategic approach with the supported literature. IVIF decision making trial and evaluation laboratory (DEMATEL) is constructed for measuring the relative importance of criteria and dimensions. IVIF VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) is applied for ranking the corporate governance-based performance of sustainable energy industries in emerging economies. Sensitivity analysis is also used for understanding the coherence of ranking results. Analysis results illustrate that the energy industry could provide more sustainable results than the conventional managerial policies by considering the social capital of board members. Additionally, mass-economies are closely related to the sustainable production capacities of energy industry and have the best performance results for the corporate governance-based sustainable energy production strategies. The results are discussed to provide the policy recommendations by comparing analysis results of emerging economies for further studies.
Keywords: Sustainability; Energy Industry; Production; Emerging Economies; Corporate Governance; Ivif dematel; Ivif vikor